Evaluation of scarification methods for seeds of algarrobo (Hymenaea courbaril L.) (Revista de Investigaciones Universidad del Quindío, 2010)
A study was carried out attempting to evaluate the effectiveness of three methods of scarification: mechanical, physical and chemical over the germination of algarrobo seeds (Hymenaea courbaril). 20 seeds were taken per treatment, being 10 of them the replay (200 seeds in total). Once applied the respective treatments in each of the evaluated methods, the seeds were put with soil into plastic containers and taken to the University of Quindío greenhouse later on. A month later, data of germinated, no germinated and dead seeds percentage were taken, finding out that among the used methods, the chemical method showed better results, and among the treatments the most effective was: H2SO4.
Keywords: Scarification; physical; Chemical; mechanical; seed; germination